2000
DOI: 10.1161/01.atv.20.12.2670
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of ApoA-I–Containing HDL Subpopulations in Patients With Coronary Heart Disease

Abstract: Abstract-High density lipoproteins (HDLs) and their subspecies play a role in the development of coronary heart disease (CHD). HDL subpopulations were measured by 2-dimensional nondenaturing gel electrophoresis in 79 male control subjects and 76 male CHD patients to test the hypothesis that greater differences in apolipoprotein (apo)A-I-containing HDL subpopulations would exist between these 2 groups than for traditional lipid levels. In CHD subjects, HDL cholesterol (HDL-C) was lower (Ϫ14%, PϽ0.001), whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
134
0
6

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(147 citation statements)
references
References 45 publications
7
134
0
6
Order By: Relevance
“…It is, however, premature to draw conclusions regarding the relationship between pre␤ 1 -HDL concentration and atherosclerosis. Asztalos et al reported either no difference in pre␤ 1 -HDL between men with or without CAD 24 or a higher pre␤ 1 -HDL/␣ 1 -HDL ratio in subjects with more severe coronary artery stenosis. 25 Miida et al have reported higher pre␤ 1 -HDL values among Japanese men with CAD.…”
Section: Discussionmentioning
confidence: 96%
“…It is, however, premature to draw conclusions regarding the relationship between pre␤ 1 -HDL concentration and atherosclerosis. Asztalos et al reported either no difference in pre␤ 1 -HDL between men with or without CAD 24 or a higher pre␤ 1 -HDL/␣ 1 -HDL ratio in subjects with more severe coronary artery stenosis. 25 Miida et al have reported higher pre␤ 1 -HDL values among Japanese men with CAD.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, in vivo kinetic studies demonstrated the decreased production as well as increased clearance of VLDL, an observation consistent with the inhibition of VLDL secretion via the strong inhibition of HMG-Co reductase activity and increased direct uptake by an up-regulated LDL receptor 12,13) . Cardioprotective HDL is heterogeneous in size and apolipoprotein composition, which would, in turn, affect atherosclerosis differently; for example, large HDL, but not small HDL, is a predictor of cardiovascular risk [14][15][16] . In this context, atorvastatin may exert a cardioprotective effect by increasing large HDL (HDL4).…”
Section: Discussionmentioning
confidence: 99%
“…Increased HDL2 might promote non-specific cholesterol efflux from the cells 24) . In regard to the clinical significance of the plasma pre 1-HDL concentration and its disappearance, supposing conversion to -HDL, accumulating evidence suggests that impaired conversion of pre 1-HDL resulting in high plasma pre 1-HDL concen- tration is involved in the initiation and progression of atherosclerosis [25][26][27] . In this study, pitavastatin also significantly decreased plasma pre 1-HDL concentration, but significantly increased the disappearance rate of pre 1-HDL.…”
Section: Discussionmentioning
confidence: 99%